KANDUNGAN SENYAWA ALKALOIDA, TANIN SERTA NILAI NUTRISI BEBERAPA JENIS HIJAUAN YANG DIBERIKAN PADATERNAK DL PULAU TIMOR (THE CONTENTS OF ALKALOID, TANNIN AND ITS NUTRITIONAL- VALUES FROM SEVERAL BROWSE FED TO LIVESTOCK IN TIMOR ISLAND) - Jamal, Yuliasri; Semiadi, Gono (Research Center for Biology-Indonesian Institute of Sciences, 1997)
A study was conducted in determining the contents of alkaloid, tannin and nutritional Values from six browses fed to fattening cattle in Timor island. The samples Were gmelina (Gmelina arborea Roxb.),pates/lamtoro (Leucaena leucocephala [Lamk.J De Wit),daun kupu-kupu (Bauhinia malabarica Roxb.), gala-galaAuri (Sesbania grandiflora [Li Pers.l gamal (Gliriddia sep/um [lick] Steud.).and kabesak (Acacialeucoohloea Willd.).Samples were collected during wet and dry seasons.Results showed that total number of alkaloid compounds varied from 14 to 30.There was an increase in concentration for alkaloid and tannin from Wet to dry season, however the concentrations were low (< 1%).The increase in the concentrations between seasons Were ranged from 20% to 32096.Nutritional values of the browse during wet season were considered high, however there is a need in evaluating the nutritional values of the browses during dry season as well.